Career Development for Retaining Local Talents in the Private Sector: Study from the Kingdom of Bahrain - Al-Aali, La’aleh (CENTRAL ASIA AND THE CAUCASUS, 2024)
The paper focuses on one GCC state, Kingdom of Bahrain to examine career development in private sector for retaining local talents. This research aims at examining career development function specifically as a retention tool. Career development as an integrated practice within human resource development is analyzed by examining career development practices within the human resource development function. It explores career development as a retention tool towards facing the challenge of low employee retention rate in private sector. The paper reveals the integrated practice of human resource development to achieve career development within private sector. It also surfaces the consideration of monetary rewards as part of the integrated practice of career development within human resource development function. The research methodology is mixed method. The quantitative data was analyzed from 467 returned questionnaires. Five to eight managerial level semi structured interviews were conducted in each of the seven private organizations where questionnaires were distributed, totaling 38 interviewees. Hence, the paper presents findings within career development from perspective of both employee and employer.